1990
DOI: 10.1103/physrevb.41.5661
|View full text |Cite
|
Sign up to set email alerts
|

Structure of liquid equiatomic KSn and CsSn

Abstract: The structure factors of liquid equiatomic KSn and CsSn alloys have been determined by neutron diffraction. A distinct peak at about 1 A, the first sharp diffraction peak (FSDP), occurs in all measured structure factors. The temperature dependence of the structure has been studied for KSn: apart from the FSDP, whose position shifts toward smaller wave vector and magnitude decreases with increasing temperature, the structure factor remains essentially unaltered. The radial distribution function clearly shows th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Nevertheless we propose that this method of extracting chain lengths from RMC modeling of total scattering data may prove valuable for identifying other molten chemical species, especially if the cluster of interest is small. Early total scattering studies found signatures of Zintl polyanions in the A-Sn, and A-Te systems (where A is an alkali metal), both of which are viable fluxes for crystal growth. ,, Constraints on the number of distinct anion coordinations might be gleaned from X-ray absorption spectroscopy or nuclear magnetic resonance, although the latter is not straightforward for sulfides …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless we propose that this method of extracting chain lengths from RMC modeling of total scattering data may prove valuable for identifying other molten chemical species, especially if the cluster of interest is small. Early total scattering studies found signatures of Zintl polyanions in the A-Sn, and A-Te systems (where A is an alkali metal), both of which are viable fluxes for crystal growth. ,, Constraints on the number of distinct anion coordinations might be gleaned from X-ray absorption spectroscopy or nuclear magnetic resonance, although the latter is not straightforward for sulfides …”
Section: Resultsmentioning
confidence: 99%
“…In view of the difficulties associated with constant-pressure ab initio MD simulation, we decided to repeat both runs at the experimental atomic volume. Experimentally, the number density of the molten alloy has been estimated from the neutron diffraction data (essentially from the slope of the reduced radial distribution function G(R) = 4π Rn(g(R) − 1) at small R where g(R) is the total pair correlation function), leading to an atomic volume of L = 42.6 Å 3 [11] compared to S = 37.84 Å 3 for the crystalline compound at room temperature [39]. However, it is certainly legitimate to emphasize that the experimental densities determined in that way are subject to a rather large uncertainty.…”
Section: Simulation Historymentioning
confidence: 99%
“…Hightemperature phase transitions to plastic (rotor) phases with diffusive disorder of the alkali ions and rotational motion of the polyanions have been detected in NaSn and CsPb [3,4]. Diffraction experiments on molten alkali-Sn and alkali-Pb alloys have demonstrated the existence of a pronounced chemical and topological short-range order (CSRO and TSRO), which has been interpreted as evidence for the at least partial survival of the polyanions in the liquid phase [5][6][7][8][9][10][11][12][13]. This interpretation is supported by the analysis of the thermodynamic and electronic transport properties; see I for a more detailed discussion and references.…”
Section: Introductionmentioning
confidence: 99%
“…The radial distribution functions each exhibit a peak at a distance equal to the tetrahedral Pb-Pb bond length. Similar experiments have been carried out for alkali-tin alloys [42]. No measurements of the partial structure factors, for instance by means of isotope substitution, have as yet been reported.…”
Section: The 'Perfect Zintl Model'mentioning
confidence: 64%